Intersections of ψ classes on Hassett spaces of rational curves - Sharma, Nand, author; Cavalieri, Renzo, advisor; Peterson, Chris, committee member; Achter, Jeff, committee member; Prasad, Ashok, committee member (Colorado State University. Libraries, 2018)
Hassett spaces are moduli spaces of weighted stable pointed curves. In this work, we consider such spaces of curves of genus 0 with weights all 1/q , q being a positive integer greater than or equal to 2. These spaces are interesting as they have different universal families and different intersection theory when compared with classical moduli spaces of pointed stable rational curves. We develop closed formulas for intersections of ψ-classes on such spaces. In our main result, we encode the formula for top intersections in a generating function obtained by applying an exponential differential operator to the Witten-potential.